2005
DOI: 10.1634/stemcells.2005-0301
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant Genomic Imprinting in Rhesus Monkey Embryonic Stem Cells

Abstract: Genomic imprinting involves modification of a gene or a chromosomal region that results in the differential expression of parental alleles. Disruption or inappropriate expression of imprinted genes is associated with several clinically significant syndromes and tumorigenesis in humans. Additionally, abnormal imprinting occurs in mouse embryonic stem cells (ESCs) and in clonally derived animals. Imprinted gene expression patterns in primate ESCs are largely unknown, despite the clinical potential of the latter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
30
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 42 publications
6
30
0
Order By: Relevance
“…Consistent with neonatal rhesus tissues and ES cells, IGF2 and H19 are monoallelically expressed in all cynomolgus extraembryonic tissues analyzed (Fujimoto et al 2005(Fujimoto et al , 2006. H19 expression is also consistently monoallelic in all somatic tissues tested, although the corresponding tissue imprinting of IGF2 is somewhat relaxed, particularly in liver and skeletal muscle ( Fig.…”
Section: Paternally Imprinted Genessupporting
confidence: 67%
“…Consistent with neonatal rhesus tissues and ES cells, IGF2 and H19 are monoallelically expressed in all cynomolgus extraembryonic tissues analyzed (Fujimoto et al 2005(Fujimoto et al , 2006. H19 expression is also consistently monoallelic in all somatic tissues tested, although the corresponding tissue imprinting of IGF2 is somewhat relaxed, particularly in liver and skeletal muscle ( Fig.…”
Section: Paternally Imprinted Genessupporting
confidence: 67%
“…All of the HUES-lines were derived from frozen, grade 3-4 blastocysts supernumerary from fertility treatments (Cowan et al 2004). Given several recent reports of increased incidence of imprinting errors in in vitro cultured animal embryos (Young et al 2001;Mann et al 2003Mann et al , 2004Fujimoto et al 2006), children conceived through assisted reproduction technologies (DeBaun et al 2003;Maher 2005;Robertson 2005), in superovulated human oocytes (Sato et al 2007), and in the spermatozoa of oligospermic men (Marques et al 2004), more studies on imprinting in the human embryo are now required to evaluate the biorisk for stem cell derivations. Imprinting variability was not restricted to the HUES-lines and thus cannot be attributed to the use of trypsin passaging on mouse embryonic fibroblast feeders that was unique to these lines (Cowan et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…However, this phenomenon has been previously observed, for example Large Offspring Syndrome (LOS) induced by in vitro embryo culture or somatic cell nuclear transfer in sheep (Young et al 2001(Young et al , 2003 disrupts the IGF2R gene that is rarely affected in humans or mice (Gicquel et al 2004). The disruption of IGF2, H19, and other 11p15.5/mouse distal chromosome 7 genes that is relatively more common in humans, rhesus monkeys, and mice (Dean et al 1998;Humpherys et al 2001; Mann et al 2003;Ogawa et al 2003;Mann et al 2004;Fujimoto et al 2006) has not been observed in sheep. Since one possibility is the appropriation of different imprinting regulatory mechanisms between genes in the preimplantation embryo, we examined the status of a candidate epigenetic mechanism, CpG methylation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…cells were documented to be perturbed [11,12]. Research on a small number of imprinted genes showed that hES cells have a more stable imprinting status compared with mouse ES cells [13].…”
Section: Introductionmentioning
confidence: 99%